Fetal exposure to androgens, as indicated by digit ratios (2D:4D), increases men's agreeableness with women. (March 2015) - Moskowitz, D.S.; Sutton, Rachel; Zuroff, David C.; Young, Simon N.
Highlights: Smaller 2D:4D ratios reflect greater prenatal androgen exposure. We examined associations among 2D:4D ratios, agreeableness, and gender of partner. Men with smaller digit ratios showed greater agreeableness with women than with men. Men with smaller digit ratios showed lower quarrelsomeness with women than with men. Fetal androgen exposure affects context specific aspects of men's social behavior. Abstract: The ratio of the length of the second finger, or digit, to the fourth finger (2D:4D) is influenced by fetal exposure to androgens; a smaller ratio indicates greater androgen exposure. We used event contingent recording to investigate the relation between the 2D:4D ratio and social behavior. Participants completed multiple records of their behavior in events in naturalistic settings; records included information about situational features such as the gender of the person with whom the person was interacting. Men were more agreeable towards women than men; this effect was significantly greater in those with smaller 2D:4D ratios. Men with smaller 2D:4D ratios were also less quarrelsome towards women than towards men. The 2D:4D ratio did not influence social behavior in women. The hormonal environment in which the male fetal brain develops may influence adult social behavior in specific contexts.